COVID and Christ: Remote, Faith-Based Activities Using Religious Technology in the Catholic Church - McNeill, Stephen J. (European Journal of Social Science Education and Research, 2022)
Only 39 percent of American Catholics say they attend church in any given week (Gallup, 2019). In an effort to connect and engage the global congregation of the Catholic Church, the Vatican partnered with an external developer to create mobile learning tools—a project cumulating with the iOS and Android app "Click to Pray” and hardware extension app “eRosary.” Click to Pray is the prayer platform of the “Pope’s Worldwide Prayer Network” (PWPN), a pontifical work whose mission is to mobilize Catholics through prayer and action. Founded in 1844 as the Apostleship of Prayer, the PWPN is present in 98 countries and is made up of more than 35 million Catholics. This study aims to review the technology and security of the software; design of the hardware; the end-user experience, and the primary demographics of those who have downloaded either the Click to Pray or eRosary apps. This paper will also examine the idea of authenticity and replication of the religious experience in a remote atmosphere, in addition to its uses and gratifications. The eRosary is also capable of monitoring the health of the user, providing an interesting example of mobile learning device convergence for mind, body, and spirit.
Keywords: biometric user interfaces, wearable technology, religious technology, mobile learning, data privacy